Indonesia and the 1997-98 El Nino: fire problems require long-term solutions - Byron, R.N.; Shepherd, G. (Overseas Development Institute, 1998)
The 1997-98 El Nino is among the strongest recorded and low rainfall in Indonesia set the conditions for widespread fires. At the same time, it is clearer druing this particular El Nino than it has been in the past that many fires are being deliberately set. They must be understood in the context of competing land-claims from government and private companies on the one hand, and local people with customary rights to land on the other. The 1997 El Nino is the first in which the resources of land satellite imagery and the internet have been harnessed to demonstrate quite clearly where the fires are taking place, and why.